2007
DOI: 10.1016/j.febslet.2007.10.063
|View full text |Cite
|
Sign up to set email alerts
|

CarO, an Acinetobacter baumannii outer membrane protein involved in carbapenem resistance, is essential for l‐ornithine uptake

Abstract: We previously associated the emergence of carbapenem resistance in Acinetobacter baumannii with the loss of an outer membrane (OM) protein designated CarO. CarO was found essential for L L-ornithine uptake: CarO-deficient strains were specifically impaired to grow only on L L-ornithine, and failed to incorporate L L-[ 14 C] ornithine from the medium. L L-arginine, and histidine and lysine to a lower extent, could effectively compete for L L-[ 14 C] ornithine uptake. L L-ornithine also reduced A. baumannii sens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
84
1
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 89 publications
(91 citation statements)
references
References 24 publications
5
84
1
1
Order By: Relevance
“…We also demonstrated that CarO is involved in the OM permeation of L-ornithine, a basic amino acid that displays structural similarity with carbapenems (31). These observations led us to hypothesize that CarO may allow carbapenem influx across the A. baumannii OM and that strains in which the carO gene was inactivated could have been selected under carbapenem pressure (29,31).…”
mentioning
confidence: 97%
See 3 more Smart Citations
“…We also demonstrated that CarO is involved in the OM permeation of L-ornithine, a basic amino acid that displays structural similarity with carbapenems (31). These observations led us to hypothesize that CarO may allow carbapenem influx across the A. baumannii OM and that strains in which the carO gene was inactivated could have been selected under carbapenem pressure (29,31).…”
mentioning
confidence: 97%
“…We also demonstrated that CarO is involved in the OM permeation of L-ornithine, a basic amino acid that displays structural similarity with carbapenems (31). These observations led us to hypothesize that CarO may allow carbapenem influx across the A. baumannii OM and that strains in which the carO gene was inactivated could have been selected under carbapenem pressure (29,31). However, carO was not always interrupted in all of our clonally related carbapenem-resistant A. baumannii isolates (29), indicating that a mechanism(s) other than carO disruptions can also account for the reduced carbapenem susceptibility phenotype.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Carbapenem resistance is generally mediated by class D ß-lactamase such as the OXA-23, -24, -25, -26, -27 and -40 (Van Looveren and Goossens, 2004). Resistance to both imipenem and meropenem in multidrug-resistant clinical strains of A. baumannii can also be associated with changes in the outer membrane composition, such as the loss of a heat-modifiable 29-kDa outer membrane protein designated CarO (Limansky et al, 2002;Mussi et al, 2005), which mediates uptake of carbapenems as well as L-ornithine and other basic amino acids (Mussi et al, 2007). Carbapenem used to be the antibiotic of choice for the treatment of Acinetobacter infections.…”
Section: Mechanisms and Genetics Of Antibiotic Resistancementioning
confidence: 99%